A Highly Diverse and Functional Naïve Ubiquitin Variant Library for Generation of Intracellular Affinity Reagents. Issue 1 (6th January 2017) - Leung, Isabel; Jarvik, Nick; Sidhu, Sachdev S.
Abstract: We report the design, construction, and validation of a highly diverse phage-displayed naïve ubiquitin variant (Ubv) library. We first conducted a mutation tolerance scan of 27 residues and confirmed that 24 of these could be substituted by chemically diverse amino acids without compromising the display of Ubvs on phage. Subsequently, we constructed a library containing 6.8 × 10 10 unique members, in which these 24 positions were diversified with a degenerate codon that encodes for 6 aa that are prevalent in protein interaction sites. To ensure the optimal structural stability of the Ubvs, we constructed the library in a two-step process, whereby 12 positions were randomized first, and following the selection for displayed Ubvs, the resulting pool was further diversified at the other 12 positions. The resulting library was validated by conducting binding selections against a panel of 40 diverse protein antigens and was found to be as functional as a highly validated synthetic antibody library, yielding binders against 30 of the antigens. Detailed characterization of an Ubv that bound to the cell-surface receptor human epidermal growth factor receptor 3 revealed tight binding in the single-digit nanomolar range. Moreover, Ubvs that bound to two distinct sites on the intracellular adapter Grb2 could be combined to generate a potent inhibitor that functioned in cells. These results validate ubiquitin as a robust scaffold for the construction of naïve libraries that can be used to generate Ubvs that target signaling networks both outside and inside the cells. Graphical Abstract: Highlights: There is a great need for affinity reagents that can target proteins inside cells. We constructed a naïve library containing billions of Ubvs. We generated Ubvs that targeted the extracellular receptor human epidermal growth factor receptor 3. We generated Ubvs that inhibited the intracellular adapter Grb2. The naïve Ubv library can target diverse proteins inside cells.